Happy Accountants, Better Results? Unpacking the Link Between Happiness and Performance - Dian Widiyati; Intan Siti Aropah; Siti Nurhasanah (CV. Ulil Albab Corp, 2025)
This study aims to analyze the effect of happiness on accountants’ performance using the framework of Positive Psychology Theory. Happiness in this research is measured through six main dimensions: Pleasure, Meaning, Subjective Happiness, Life Satisfaction, Need for Cognition, and Perceived Relative Income. These dimensions represent emotional, cognitive, and social aspects that potentially influence psychological well-being and professional performance among accountants. The study employs a quantitative causal explanatory approach. Primary data were collected through questionnaires distributed to 181 professional accountants working across various sectors, both financial and non-financial. Data analysis was conducted using multiple linear regression. The results show that Meaning, Pleasure, and Perceived Relative Income have a positive and significant effect on accountants’ performance. This finding indicates that accountants who find meaning in their work, experience pleasure in performing their duties, and perceive their income as fair and competitive tend to demonstrate higher levels of performance. Conversely, Subjective Happiness, Life Satisfaction, and Need for Cognition do not have a significant effect on performance. This suggests that personal happiness, general life satisfaction, and the tendency to engage in deep thinking do not directly contribute to productivity but may serve as supporting factors for long-term psychological well-being. The study emphasizes the importance of applying Positive Psychology principles in human resource management within the accounting profession. Organizations should strengthen aspects of work meaning and happiness by fostering a supportive environment, ensuring fair reward systems, and providing opportunities for professional growth.